(untitled) (Texas Journal of Engineering and Technology, 2024)
The distinction between isolated and non-isolated definitions plays a crucial role in various academic and professional fields, influencing the clarity, understanding, and application of the concepts. This article examines the fundamental differences between these two definitional approaches, examining their characteristics, advantages, and limitations. Computer science, systems engineering, and mathematics, the study clarifies the contexts in which each type of definition is most effective. The results highlight the importance of choosing appropriate definition frameworks to improve understanding and facilitate the resolution of complex problems. In conclusion, the article proposes best practices for implementing isolated and non-isolated definitions in educational and technical settings